Librarian professionalism internship program at SMP Negeri 40 Bandung - Nisrina Sifahumaria; Siti Nuraeni Azzahro (Dedicated: Journal of Community Services (Pengabdian kepada Masyarakat), 2025)
Internship activities are essential for channeling students' knowledge acquired during their studies into the workforce, particularly in fields related to their chosen majors. This article aims to present the results of an internship at the SMP Negeri 40 Bandung library. The method used in this internship activity began with observing the library space, analyzing the problems and needs of the library, and designing a program that addressed those needs. The internship at the SMP Negeri 40 Bandung library provided valuable experiences and learning, offering positive insights for students regarding the role and existence of a school library. Several internship outcomes included organizing and preserving library materials, circulation services focused on book borrowing and returns, and implementing Information and Communication Technology (ICT) in the library, particularly through OPAC (Online Public Access Catalog). However, the internship outcomes were not fully maximized due to several factors, including limited access and other constraints from the school.   Abstrak Kegiatan magang sangat diperlukan untuk menyalurkan pengetahuan mahasiswa selama perkuliahan dalam dunia kerja yang relevan dengan jurusan yang diambil. Artikel ini bertujuan untuk memaparkan hasil kegiatan magang yang telah dilaksanakan di perpustakaan SMP Negeri 40 Bandung. Metode pengabdian yang digunakan pada kegiatan magang ini yaitu diawali dengan mengamati ruang perpustakaan, menganalisis masalah dan kebutuhan perpustakaan serta merancang program yang sesuai dengan kebutuhan. Kegiatan magang yang telah terlaksana di perpustakaan SMP Negeri 40 Bandung ini telah memberikan banyak pengalaman dan pembelajaran yang bernilai positif bagi pandangan serta wawasan mahasiswa terhadap keberadaan suatu perpustakaan sekolah. Beberapa hasil yang telah dilaksanakan dari kegiatan magang ini yaitu program pengorganisasian bahan pustaka di perpustakaan, pelestarian bahan pustaka, layanan sirkulasi di perpustakaan yang berfokus pada peminjaman dan pengembalian buku, serta penerapan Teknologi Informasi dan Komunikasi (TIK) di perpustakaan dengan mengoperasikan OPAC (Online Access Public Catalog). Namun, dari hasil magang tersebut tidak terlalu maksimal dikarenakan banyak faktor yang kurang bisa dipenuhi dari pihak sekolah karena keterbatasan akses dan lain sebagainya. Kata Kunci: kegiatan perpustakaan; perpustakaan sekolah; program magang